PREVALENCE OF OBESITY IN ADULT PATIENTS WITH DIABETES MELLITUS TYPE 2 AND AUTOIMMUNE CHRONIC THYROIDITIS - Gherbon Adriana (European Scientific Journal, ESJ, 2013)
Background&Aims: The higher prevalence of obesity is associated with a number of cardiovascular risk factors. The purpose of this study is to asses the prevalence of obesity in adult patients with diabetes mellitus (DM) type 2 and autoimmune chronic thyroiditis (ACT). Methods: The studied group was represented by 78 adult patients with DM type 2 and ACT (70 women and 8 men). Were used clinical, biochemical and imaging parameters. Results: 53 (67.94%) (45 women and 8 men) had different types of obesity. The obesity was more frequent in men than in women (100% vs. 64.28%, p = 0.04, X2 = 4.2). In function of obesity type, android obesity was prevailed (94.34 % of cases), following by gynoid obesity type (5.66 %). Also, 26.92 % were overweight (all women). Regarding the type of android obesity, 39.62 % had type I, 37.73 % type II and 22.64 % type III. Also, 64.15 % had hypertension and dyslipidemia 79.24 %. Conclusions: In patients with DM type 2 and ACT the obesity prevailed in men. It was android type, represented an increased risk of cardiovascular morbiditymortality, particularly for atherosclerotic cardiovascular disease. The association of thyroid disease, which over time can evolve with hypothyroidism, is an additional risk factor for atherosclerotic cardiovascular disease.